KAJIAN VIKTOMOLOGI TERHADAP ANAK SEBAGAI KORBAN INCEST OLEH AYAH KANDUNGNYA DI KABUPATEN BULELENG - Nina Septiani Marista Sigumonrong; Made Sugi Hartono; I Nengah Suastika (Jurnal Ilmu Hukum Sui Generis, 2025)
This study aims to (1) determine and analyze the factors that cause incest by the biological father and (2) review and analyze legal and social efforts to prevent the occurrence of incest victims by their biological father in Buleleng Regency. The research method used is empirical legal research with qualitative descriptive method. Data were collected through in- depth interviews with police officers and social workers, as well as through the study of legal documents, literature, and related secondary sources. Non-probability sampling and purposive sampling techniques were applied for the selection of subjects, so as to obtain a comprehensive picture of the incest phenomenon. The results revealed that (1) children's vulnerability to incest by biological fathers in Buleleng Regency is influenced by their young age and lack of understanding of bodily rights, so they are unaware of physical and psychological abuse. Divorce and sole custody create emotional and economic dependency, making victims reluctant to seek help. Closed family environments and minimal supervision make early detection of abuse difficult. Lack of sex and rights education at home and school adds to the abuse gap. Patriarchal norms and cultural stigma force victims to remain silent. (2) Legal protection of child victims of incest in Buleleng is designed through prevention and decisive action with the principle of victimology. Prevention includes education of parents, educators, community leaders, and officials about children's rights, body privacy, and criminal sanctions. Repressive actions by the Buleleng Police Women and Children Protection Unit include investigation, prosecution and investigation, along with psychosocial rehabilitation services from the Social Affairs Office. This approach ensures comprehensive protection of victims' rights, providing restitution, compensation and mental recovery, while preventing repeated and ongoing violence.